Modernist islamic perspective: Assessing bangsamoro jihad in the Southern Philippines - Abdul M, Lantong; Omar, Rusdi (Institute of Advanced Scientific Research, Inc., 2019)
As the founder and ideologue of the contemporary Islamic revival vanguard in the Southern Philippines, the views of ShaykhSalamatHashim on jihad (armed struggle) have profoundly influenced the course of the decadesold armed resistance movement in the Southern Philippines. Despite his advocacy on a peaceful resolution to the Bangsamoro conflict, his real motive has been hotly debated among scholars and political observers. Thus, the purpose of this article is to examine and analyze Hashim’s views on jihad, using Modernist Islamic theory. Hashim’s views on jihad included his views on the nature of jihad, shari’ah ruling on it, its legitimacy, objectives, enemies, ethics and its termination. In view of this, the article found that in resolving the Bangsamoro question, Hashim viewed peace, not war, as Islam's primary policy. In fact, Hashim strongly emphasized that jihad in the form of armed fighting is for self-defense against aggression, oppression, persecution and injustice. Thus, for him, jihad as a defensive or self-defense is an essential mechanism of Islam for the survival of the Muslim Ummah, in general, and the Bangsamoro community, in particular.